The mass media and tendentious modernity in the transition process from the national society to the European Community - Constantin Schifirnet (Pontifícia Universidade Católica do Rio Grande do Sul, 2009)
This paper analyses the transformations of mass media in the process of constructing the European identity after the two enlargements. I will focus on the impact of mass communication on Europeanization. I study the transition in Romania in particular to understand Europeanization, otherwise it sounds as if my study covers the broad scope in Europe, and case study is Romanian media. My thesis is that mass media could play an active role in promoting the European integration process if it shifted its attention from reflecting historical particularities to reflecting upon the modern evolution of each EU member. I introduce the concept of tendentious modernity, useful in studying mass communication in transitional societies. In such societies, modernization began with political institutional construction and not with the building of the capitalist economy. Modernity is the framework and main element upon which a nation is supported, a mosaic however not by means of economy, the basis of a national development and progress. In these societies, such as Romania, mass media promote this mosaic modernity, and, at the same time they, acts the primary messenger of modernity and Europeanization.